Some Steps for Language Maintenance in The Society and Individual - Ramlan Ramlan (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2018)
Language is an arrangement of arbitrary symbols possessing an agreed-upon significance within a community. These symbols can be used and understood independent of immediate contexts, and are connected in regular ways. Naturally individual has the typical language characteristics which is influenced by the feeling, idea, emotion, situation and condition, articulation and cognition. Reading and speaking often and widely the textbook, watching/listening to television, films, radio and podcasts, networking and making friends with people, and starting a local language club are the tips for maintaining the individual’s language. The accent, dialect, and status of language are comprehended as the reflection of individual language and consequently are closely realted to the society. The use of tribal language in the traditional ceremony, party, religious services, daily activities, local billboards are the tips for maintaining language in the society. A good language status is greatly affected by the individual’s language competence and performance. Therefore, individual in a certain society is in charge to maintain the language.